Processing and turn-over of small non-coding RNA OxyS in E. coli & post-transcriptional regulation of RpoS levels by small non-coding RNAs OxyS and DsrA and the Hfq protein in E. coli - Basineni, Sobha Rani; Justus Liebig University Giessen (My University, 2010)
rpoS mRNA is one of the first target RNA shown to be regulated by at least 3 small noncodingRNAs under various stress conditions. Two out of three sRNAs are involved in theactivation of rpoS mRNA translation. By contrast the third sRNA, OxyS has been implicatedin the repression of RpoS synthesis. OxyS RNA is strictly induced under oxidative stress andreduces the levels of the stationary phase sigma factor RpoS. In order to reveal a possibleimpact of processing on growth-dependent regulation, we analyzed the turn-over rates ofOxyS and rpoS mRNA in early exponential and in stationary growth phase in different E. colistrains. We were not able to assign a major role to any of the individual endo- orexoribonucleases (RNase E, RNase III, PNPase or RNase II) on OxyS turn-over inexponential growth phase. However, the simultaneous lack of RNase E, PNPase and RNase IIactivity resulted in some stabilization of OxyS in exponential growth phase, indicating thecombined action of both endo- and exoribonucleases on OxyS turn-over. A greater impact ofRNase E on OxyS turn-over was observed in stationary phase and this in turn was dependenton the presence of the RNA chaperone Hfq and of DsrA sRNAs (activator of rpoS mRNAtranslation). Our data also confirm a role of RNase III in rpoS turn-over, however, only inexponential growth phase. We conclude that OxyS and rpoS mRNA turn-over rates areinfluenced by different RNases and additional factors such as Hfq and DsrA and that theimpact of these factors is strongly dependent on growth phase.Furthermore, we analyzed the influence of OxyS inhibitor RpoS synthesis and Hfq andDsrA activators of RpoS synthesis, while all three regulators co-exist under oxidativestress. Our data reveal that growth phase has a strong effect on RpoS levels, while no majorinfluence of oxidative stress generated by H2O2 is observed. The lack of DsrA resulted in asmall decrease of RpoS levels, which is in agreement with the activating effect of this sRNAon RpoS translation. A lack of Hfq resulted in significantly reduced levels of RpoS, althoughthe turn-over of RpoS was reduced compared to the parental wild type. DsrA and OxySinfluenced RpoS turn-over in opposite way by yet unknown mechanisms. These findingsillustrate that main control of growth-phase dependent RpoS expression is at level of rpoStranscription and that growth phase has a stronger impact on RpoS levels than oxidativestress.

RpoS ist ein bedeutender Sigmafaktor der stationären Wachstumsphase in E. coli. Die rpoSmRNA ist eine der ersten RNAs für die unter verschiedenen Stressbedingungen eineRegulation durch mindestens drei small non-coding RNAs gezeigt wurde. Zwei dieser dreisRNAs sind an der Aktivierung der rpoS mRNA Translation beteiligt. Im Gegensatz dazureprimiert die dritte sRNA die RpoS Synthese. Diese OxyS RNA wird unter oxidativemStress induziert und reduziert die Menge an RpoS.Um einen möglichen positiven Einfluss der RNA-Prozessierung auf derenWachstumsphasen-abhängige Regulation nachzuweisen, wurden in dieser Arbeit dieUmsatzraten von OxyS und rpoS in der frühen exponentiellen sowie in der stationärenWachstumsphase in verschiedenen E. coli Stämmen untersucht. Hierbei war es zwar nichtmöglich einer einzelnen Endo- oder Exoribonukleasen (RNase E, RNase III, PNPase oderRNase II) eine Hauptrolle im OxyS-Umsatz zuzuweisen, das gleichzeitige Fehlen derAktivitäten von RNase E, PNPase und RNase II resultierte jedoch in einer Stabilisierung vonOxyS in der exponentiellen Wachstumsphase. Dies lässt auf eine kombinierte Wirkung derAktivitäten von Endo- und Exoribonukleasen auf den OxyS-Umsatz schließen. Ein größererEinfluss von RNase E auf den OxyS-Umsatz konnte in der stationären Wachstumsphasenachgewiesen werden, der außerdem von der Anwesenheit des RNA-Chaperons Hfq und vonder DsrA sRNA (Aktivator der rpoS mRNA-Translation) abhängig ist. Des Weiteren konnteausschließlich in der exponentiellen Wachstumsphase eine Beteiligung von RNase III amOxyS-Umsatz nachgewiesen werden. Die OxyS und rpoS mRNA-Umsätze werden demnachsowohl von verschiedenen RNasen als auch von weiteren Faktoren wie Hfq und DsrAreguliert. Der Einfluss der einzelnen Faktoren ist wiederum stark von der Wachstumsphaseabhängig.Da alle drei Regulatoren von RpoS, OxyS, DsrA und Hfq, unter oxidativem Stress existierenaber sowohl aktivierenden wie inhibierenden Einfluss auf RpoS haben, wurde in dieserArbeit ebenfalls deren Synthese untersucht. Oxidativer Stress, hervorgerufen durch H2O2,zeigte keinen starken Einfluss, wogegen ein starker Effekt der Wachstumsphase auf dieRpoS-Menge beobachtet werden konnte.Mutationsanalysen zeigten, dass in Abwesenheit von DsrA eine geringe Verminderung derRpoS-Menge stattfindet, was in Einklang mit dem aktivierenden Effekt dieser sRNA auf dieRpoS-Translation steht. Das Fehlen von Hfq resultierte sowohl in einer signifikantreduzierten Menge an RpoS als auch in einem reduzierten RpoS-Umsatz im Vergleich zumentsprechenden Wildtyp. DsrA und OxyS beeinflussen den RpoS-Umsatz in derentgegengesetzten Richtung durch bisher unbekannte Mechanismen.Die gezeigten Ergebnisse verdeutlichen, dass die Regulation der WachstumsphasenabhängigenExpression von RpoS auf Ebene der rpoS-Transkription stattfindet und sich dieWachstumsphase stärker auf RpoS auswirkt als oxidativer Stress.
Prozessierung und Umsatz der kleinen nicht-kodierenden RNA OxyS in E. coli & post-transkriptionelle Regulation der RpoS Menge durch die kleinen nicht-kodierenden RNAs OxyS und DsrA und dem Hfq Protein in E. coli
Keywords: ddc:570